Coherence times of precise depth controlled NV centers in diamond. Issue 10 (24th February 2016) - Wang, Junfeng; Zhang, Wenlong; Zhang, Jian; You, Jie; Li, Yan; Guo, Guoping; Feng, Fupan; Song, Xuerui; Lou, Liren; Zhu, Wei; Wang, Guanzhong
Abstract : Coherence times of precisely depth controlled NV centers in a diamond were investigated using oxidative etching, and it was found that they declined rapidly when the depth was about 22 nm before they finally disappeared. Abstract : We investigated the depth dependence of coherence times of nitrogen-vacancy (NV) centers through precise depth control using oxidative etching at 580 °C in air. By successive nanoscale etching, NV centers could be brought close to the diamond surface step by step, which enabled us to track the evolution of the number of NV centers remaining in the chip and to study the depth dependence of coherence times of NV centers with diamond etching. Our results showed that the coherence times of NV centers declined rapidly with the depth reduction in the last about 22 nm before they finally disappeared, which revealed a critical depth for the influence of a rapid fluctuating surface spin bath. Moreover, by using the slow etching method combined with low-energy nitrogen implantation, NV centers with depths shallower than the initially implanted depths can be generated, which are preferred for detecting external spins with higher sensitivity.